If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(3.2x-1)=36
We simplify the equation to the form, which is simple to understand
6(3.2x-1)=36
Reorder the terms in parentheses
+(+19.2x-6)=36
Remove unnecessary parentheses
+19.2x-6=+36
We move all terms containing x to the left and all other terms to the right.
+19.2x=+36+6
We simplify left and right side of the equation.
+19.2x=+42
We divide both sides of the equation by 19.2 to get x.
x=2.1875
| 64=2(3w+8)+2w | | 1/3m-4=6 | | -5x-5=-2x-15 | | 48/20=12/d | | 64=2(3w+10)+2w | | -4(1-5x)=-8(x-3) | | 8=(40+2x) | | 4x+8=5y | | -(3x-3)-(3x-6)+4=-7(x-1)-(2x+6)+3 | | 2x^2-42=-5x | | x-2/3=1/9 | | 71=(3x-11) | | 18/72=s/4 | | 50=(2x+10) | | 3(8+3r)+1=88 | | 95=u/2 | | 3(7x+8)=108 | | 0.1x+0.03+(7-x)=0.05(7) | | 3x^2-4forx=3 | | 62=(2x+4) | | 5=m/6-18 | | -(1+2m)=5(-3m+5) | | r/5=30 | | a=5(6)+3 | | -3(2+8x)+5x=108 | | 3.5x=.5+x | | 2+2(3x+10)=64 | | v+18=u | | -15+3=39 | | s/3=70 | | 24/a=6/9 | | 5x/6-1/3=-2 |